Adolescents’ mental health during the COVID-19 pandemic: Do loneliness, family, and online friends matter? - Ni Komang Yastri Anasuyari; Melly Latifah; Lilik Noor Yuliati (Humanitas: Indonesian Psychological Journal, 2023)
The COVID-19 pandemic has impacted every element of adolescent life worldwide, including Indonesia. This study intended to examine how adolescents' loneliness and mental health during the COVID-19 pandemic are affected by their family relationships and online friendships. This study collects data using an online questionnaire. The Mental Health Continuum-Short Form, the UCLA Loneliness Scale Version 3, the Brief Family Relationship Scale, and the Online Friendship Scale were used to collect the data. Two hundred ninety-two students aged 12-18 participated in data gathering in Jakarta, Indonesia, between March and April 2021. Descriptive, correlation and Structural Equation Modeling (SEM) analyses were conducted using SPSS 25.0 and LISREL 8.80. This research revealed that family relationships and online friendships had a negative effect on loneliness. Family relationships favorably impact adolescent mental health, but loneliness negatively impacts it. Furthermore, family relationships and online friendships indirectly affect adolescents' mental health through loneliness. These findings may implement in developing interventions to assist adolescent mental health during the COVID-19 pandemic in Indonesia.